Legal Liability Analysis of Insurance Contracts Signed by Agents Under a False Name (Journal of humanities and social sciences exploratio, 2025)
Combined with a litigation case where an insurance agent signed a participating annuity insurance contract in the name of the policyholder and the insured without authorization, this paper systematically analyzes the legal liabilities that agents should bear for signing insurance contracts under a false name. The paper discusses the issue from three dimensions: civil, administrative, and criminal liabilities:At the civil level, it explores the presumption rules for the validity of contracts and the principle of property return for invalid contracts;At the administrative level, it analyzes the administrative liabilities of agents for violating regulatory provisions;At the criminal level, it assesses the possibility that the agent’s act may constitute contract fraud.This paper points out that when hearing such cases, courts should comprehensively consider the facts of the case, legally presume the true intent of the parties, adhere to the principle of mutual return of property, and avoid unbalanced interests of one party. Meanwhile, insurance companies should strengthen the management and supervision of agents, improve internal control mechanisms, and prevent moral hazards such as collusive arbitrage between agents and clients.
Keywords: agency; signing under a false name; invalid insurance contract; legal liability; recovery of losses; administrative penalty; contract fraud